TiN nanopillar-enhanced laser desorption and ionization of various analytes. Issue 11 (7th April 2021) - Yamada, Yuri; Yatsugi, Kenichi; Murase, Masakazu; Mizoshita, Norihiro
Abstract : TiN nanopillar was applied as a robust analytical substrate for the laser desorption/ionization mass spectrometry of various types of analytes with a wide mass range. Numerical simulation validated the heat confinement effect of the pillar shape. Abstract : The present paper reports on the use of TiN nanopillars as a robust analytical substrate for laser desorption/ionization mass spectrometry (LDI-MS). TiN nanopillars were fabricated on silicon wafers through the dynamic oblique deposition of titanium, followed by thermal treatment in an ammonia atmosphere. The TiN nanopillars were readily applicable to a simple "dried-droplet" method in the LDI-MS without surface modification or pre-treatment. A broad range of analytes were investigated, including a small drug molecule, a synthetic polymer, sugars, peptides, and proteins. Intact molecular signals were detected with low noise interference and no fragmentation. The developed TiN-nanopillar-based approach extends the applicable mass limit to 150 kDa (immunoglobulin G) and was able to detect trypsinogen (24 kDa) at levels as low as 50 fmol μL −1 with adequate shot-to-shot signal reproducibility. In addition, we carried out MS analysis on biomolecule-spiked human blood plasma and a mixture of standard samples to investigate the promise of the TiN nanopillars for clinical research. The experimental observations are validated using electromagnetic and heat-transfer simulations. The TiN nanopillars show a reduced reflection and exhibit surges in the TiN surface temperature upon irradiation with electromagnetic radiation. Localization of thermal energy at the tips of the TiN pillars is likely to be responsible for the superior LDI performance. Our results suggest that the development of nanostructured TiN substrates will contribute to the widespread implementation of nanostructured solid substrates for biomedical and clinical applications with simple processes.